Exporting from Manufacturing Firms in Sub-Saharan Africa. - Rankin, N; Söderbom, M; Teal, F (2006)
The poor performance of many African economies has been associated with low growth of exports in general and of manufacturing exports in particular. In this paper, we draw on micro-evidence of manufacturing firms in five African countries, Kenya, Ghana, Tanzania, South Africa and Nigeria, to investigate the causes of poor exporting performance. We exploit a data set which has a much longer panel dimension than that has been used before to assess the relative importance of self-selection based on efficiency and firm size as determinants of export participation. We show that firm size is a robust determinant of the decision to export. It is not a proxy for efficiency, for capital intensity, for sector or for time-invariant unobservables. In contrast, the evidence for self-selection into exporting is very weak. Finally, our use of a longer run panel than that has been available before has allowed us to separate out the roles of ownership and skills as possible determinants of participation in exporting. We find that both foreign ownership and skills are significant determinants of exporting.